FAKTOR-FAKTOR PENYEBAB PERILAKU MEROKOK PADA REMAJA - Komasari, Dian; Helmi, Avin Fadilla (Faculty of Psychology, Universitas Gadjah Mada, 2000)
The purpose of this study was to determine which were predictors of smoking behavior on adolescents. The subjects of this study were 75 male, aged 15-18 years, and smokers. This study were done toward Scale of Parent’s Permissiveness Attitude to smoking behavior, Scale of peer influence, Scale of Psychological Satisfaction, and Scale of Smoking Behavior. The hypothesis was that parent’s permissiveness attitude to smoking behavior; influence of peer, psychological satisfaction was predictors toward smoking behavior on adolescents. There was co-linearity phenomenon between psychological satisfaction and others predictor so that psychological satisfaction out of regression analysis. The result of regression analysis showed that F value = 22,468 (p < 0,05) and R = (R = 0,620 ate R2 = 0,384). This meant that parent’s permissiveness attitude to smoking behavior and influence of peer was predictors toward smoking behavior on adolescents. It could be concluded that parent’s permissiveness attitude to smoking behavior and influence of peer were effectively contribution 38,4%. Keywords: Smoking behavior, adolescent